A recurrent mutation causing Melnick‐Needles syndrome in females confers a severe, lethal phenotype in males. Issue 4 (25th March 2018) - Spencer, Careni; Lombaard, Hendrik; Wise, Amy; Krause, Amanda; Robertson, Stephen P.
Abstract : Melnick‐Needles syndrome (MNS; MIM 309350) is an X‐linked skeletal dysplasia caused by mutations in FLNA . Females with the condition present with characteristic facial features, short stature, skeletal anomalies, including poorly modeled and sclerotic bones, and structural abnormalities such as cardiac and urological defects. Previously males were thought to present with either a mild phenotype compatible with life or a severe lethal presentation depending on the maternal phenotype. The discovery of a limited number of mutations in FLNA as the cause of the condition has clarified the molecular basis of the disorder, but only a very small number of severely affected males have been reported with MNS. Furthermore, no mildly affected males have been described with a molecular confirmation of the condition. In this report, we describe the clinical and molecular findings of a mildly affected mother with MNS and her severely affected son. They shared a well‐documented disease‐causing variant in FLNA, p.(Ala1188Thr), one of two highly recurrent mutations leading to the disorder. This is only the fourth report of a male with perinatal lethal MNS and a molecular confirmation; it is the first description of this specific mutation in a male.